Inventare als Spiegel der Wohn- und Lebenssituation des 16. Jahrhunderts in den Kommenden Würzburg und Münnerstadt - Flachenecker, Helmut (Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders, 2024)
Inventories as a reflection of the living situation of the 16th century in the Würzburg and Münnerstadt commanderies The following paper will have its focus on four inventories of commanderies, which were compiled in 1542 and 1550 for Würzburg, and in 1543 and 1544 for Münnerstadt, i.e. almost at the same time. The inventories recorded all movables belonging to the two commanderies in Franconia, and thus give a specific impression of the furnishing of most of its rooms. In all four inventories, a social distinction is clearly made between representation rooms and bedrooms, while storage rooms and courtyards complete the records. For instance, the crockery in the kitchen documents the hierarchical differences between the residents. The information reflects a more noble rather than a monastic dominated living arrangements. Overall, the inventories show relatively upscale furnishings with a significantly richness of movables, which could be an indication of a more luxurious lifestyle of the Teutonic knights. Weapons and horses can hardly be found in these Frankish commanderies.